Case Report: Exome Sequencing Identified a Novel Frameshift Mutation of α-Actin 1 in a Chinese Family With Macrothrombocytopenia and Mild Bleeding - Luo, Fang-Mei; Fan, Liang-Liang; Sheng, Yue; Dong, Yi; Liu, Lv (Frontiers in Pediatrics, 2021)
Inherited macrothrombocytopenia (IMTP) is a rare disorder characterized by a reduced platelet count and abnormally large platelets. The main clinical symptom of IMTP is mild bleeding in some patients. At present, more than thirty genes have been identified in patients with syndromic and nonsyndromic IMTP. In this study, a three-year-old boy and his mother who presented with mild epistaxis and/or gingival bleeding were diagnosed as IMTP. Wen then selected whole sequencing to explore the genetic lesion of the patients. After data filtering and mutation validation, a novel frameshift mutation (NM_001130004: c.398_399insTGCG, p.F134AfsX60) of α‑actin 1 (ACTN1) was identified in the proband and his mother but absent in other unaffected individuals. Previous studies have proved that mutations in ACTN1 may lead to IMTP with mild to absent bleeding phenotype. The novel mutation, resulting in a truncated protein in exon 4 of the ACTN1 gene, was absent in the public database such as 1000G and genomAD. Further western blot revealed that the expression of α‑actin 1 in the proband was decreased overtly, which indicated that the novel frameshift mutation may induce nonsense-mediated mRNA decay. In summary, this study not only broadened the variants spectrum of ACTN1 gene, which may contribute to the genetic counseling of IMTP, but also confirmed the diagnosis of IMTP, which may help the management and prognosis for the family members.